Clinical changes following four different periodontal therapies for the treatment of chronic periodontitis: 1-year results - Anne D. Haffajee (Blackwell Synergy, 2007)
Objective: To compare clinical changes occurring in chronic periodontitis subjects receiving SRP alone or with systemically administered azithromycin, metronidazole or a sub-antimicrobial dose of doxycycline. Material and Methods: 92 chronic periodontitis subjects were randomly assigned to receive SRP alone (N523) or combined with 500 mg azithromycin per day for 3 days (N525), 250 mg metronidazole tid for 14 days (N524) or 20 mg doxycycline bid for 3 months (N520). Gingival redness, bleeding on probing, suppuration, pocket depth and attachment level were measured at baseline and 3, 6 and 12 months post therapy. The significance of changes in clinical parameters within groups over time was sought using the Friedman test and among groups using ANCOVA or the Kruskal Wallis test. Results: All groups showed clinical improvements at 12 months, with subjects receiving adjunctive agents showing a somewhat better response. Sites with initial pocket depth 46mm showed significantly greater pocket depth reduction and greater attachment gain in subjects receiving metronidazole or azithromycin than subjects in the other groups. Some subjects showed attachment loss at 12 months in each group ranging from 15% to 39% of subjects in the SDD and SRP only groups respectively. Conclusion: This study, demonstrated that periodontal therapy provides clinical benefits and that antibiotics provide a clinical benefit over SRP alone, particularly at initially deeper periodontal pockets.